Research on Issues for Mothers in Single-Mother Households to Become Independent - Rika Masuyama; Natsuko Minamino (Budapest International Research and Critics University, 2023)
This research aims to review the literature relating to the issues for single-mother households to become independent based. Relevant articles were identified by searching the CiNii Resarch databases of articles published between 2000and 2022 examining support for the independence of single-mother households. We organized the viewpoints of